2008
DOI: 10.1103/physreve.78.060801
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of a phase-separated droplet in a polymer mixture caused by the dielectric effect of a laser

Abstract: It is found that a micrometer-sized droplet in an aqueous solution of binary polymers [water/polyethylene-glycol (PEG)/dextran] disappears upon irradiation with a focused yttrium-aluminum-garnet laser. The interface of the dextran-rich droplet broadens and disappears, and it reappears upon turning the laser off, whereas the PEG-rich droplet shrinks and disappears. These phenomena are discussed in terms of the free energy by considering the laser-induced dielectric potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Referring to the phase diagram of segregation in a dextran/PEG ATPS that was reported by Toyama et al [ 13 ], we prepared a phase diagram ( Figure 1 ) with our experimental scales and materials because the behavior of an ATPS near around a critical point and/or a binodal curve generally tends to fluctuate. To simply verify whether or not an ATPS at a certain point (composition) exhibits segregation, the following procedure is necessary: stock solutions of dextran and PEG are added with pure water to a micro-test tube, and the resulting solution is mixed vigorously using a vortex mixer and then either allowed to stand or briefly centrifuged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the phase diagram of segregation in a dextran/PEG ATPS that was reported by Toyama et al [ 13 ], we prepared a phase diagram ( Figure 1 ) with our experimental scales and materials because the behavior of an ATPS near around a critical point and/or a binodal curve generally tends to fluctuate. To simply verify whether or not an ATPS at a certain point (composition) exhibits segregation, the following procedure is necessary: stock solutions of dextran and PEG are added with pure water to a micro-test tube, and the resulting solution is mixed vigorously using a vortex mixer and then either allowed to stand or briefly centrifuged.…”
Section: Resultsmentioning
confidence: 99%
“…According to the report by Toyama et al [ 13 ], we used dextran (200,000; for leukocyte separation) and polyethylene glycol (PEG) (6000; molecular biology grade), which we obtained from Wako Pure Chemical Industries (Osaka, Japan). DNA (from salmon sperm; for molecular biology) was purchased from Wako and dissolved in water at 0.11 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that DNA aggregates which partitioned into DEX droplets were localized robustly so that they could not be pulled from the droplet to the exterior through manipulation with optical tweezers (Toyama et al 2008;Tsumoto et al 2015). As shown in the literature, the interface of droplets of PEG/DEX ATPS can serve as a filter to distinguish DNAs in long semiflexible (stiffer) forms from single-stranded short DNAs (Nakatani et al 2018), although partition coefficients are affected by coexisting salt species (Albertsson 1971).…”
Section: Research To Mimic Intracellular Structuresmentioning
confidence: 98%
“…As has been indicated by Albertsson (1971), previous literatures reveal a large number of phase diagrams for the phase separation of binary or more-component polymer solutions. The ATPS with PEG/DEX is popular in biochemical and biophysical research, and we previously used this system to investigate the dynamics (time-course development) of phase segregation of micro-scale regions (Toyama et al, 2008), as well as the specific localization of DNAs and proteins, such as the cytoskeletal protein actin (Tsumoto et al, 2015; Nakatani et al, 2018). In these studies, we observed aqueous/aqueous (water-in-water) microdroplets with an average diameter of ~10–100 μm.…”
Section: Introductionmentioning
confidence: 99%